2011
DOI: 10.1176/appi.ajp.2011.11040557
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Fear Extinction: Implications for Anxiety Disorders

Abstract: In this review we propose that the fear extinction model can be used as an experimental tool to cut across symptom dimensions of multiple anxiety disorders to enhance our understanding of the psychopathology of these disorders, and potentially facilitate the detection of biomarkers for the same. We evaluate evidence for this proposition from studies examining the neurocircuitry underlying fear extinction in rodents, healthy humans and clinical populations. Furthermore, we assess the potential use of the fear e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
258
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 342 publications
(268 citation statements)
references
References 94 publications
9
258
0
1
Order By: Relevance
“…with avoidance, trait anxiety, and risk for anxiety disorders (Graham and Milad, 2011). Because adaptive fear responses are so central to survival, and reproductive success their neural substrates are highly conserved from rodent to human (LeDoux, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…with avoidance, trait anxiety, and risk for anxiety disorders (Graham and Milad, 2011). Because adaptive fear responses are so central to survival, and reproductive success their neural substrates are highly conserved from rodent to human (LeDoux, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking SERT display elevated anxiety-like behaviors and impaired fear extinction retention (Wellman et al, 2007). Decreased expression of SERT has been reported in individuals with anxiety disorders (Kang et al, 2010), which may contribute to impaired fear extinction learning reported in these disorders (Graham and Milad, 2011). Similarly, alterations in the serotonergic circuitry is seen in individuals with AN, a disorder characterized by CR (Kaye et al, , 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual variation in the integrity of this amygdala-prefrontal circuitry has been linked to trait anxiety and posttraumatic stress disorder, suggesting that exposure-based techniques may be least effective in those who suffer from anxiety disorders (3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Like social anxiety disorder, a commonly replicated finding from various PTSD populations is hyperactivity of the amygdala in response to masked fearful faces or trauma-related stimuli [3,28,29]. This manifests as higher amygdala reactivity as compared to non-PTSD groups and/or a positive correlation between severity of PTSD symptoms and amygdala reactivity [28,[30][31][32][33].…”
Section: Amygdala Reactivity In Anxiety Disordersmentioning
confidence: 99%